Radiological and clinical prognosis of posterior lumbar intervertebral body cage versus posterior transpedicular screw fixation in patient with isthmic spondylolisthesis - Kawa Muhammed Kareem; Ameer Majeed Kareem; Samih Kakamam Hassan; Salim Mardan Omer (Advanced Medical Journal)
Background and objectives: Isthmic type of Spondylolisthesis, resulting from the failure of the anterior column, requires fixation by a transpedicular screw posteriorly. The research aimed to distinguish discrepancies in clinical presentation, functional outcomes, and mechanical characteristics by evaluating clinical, radiographic, activity, and pain information.